Learning from foreign operation modes: The virtuous path for innovation - Cristina Villar; José Pla-Barber; Pervez N. Ghauri (BRQ Business Research Quarterly, 2020)
In this article, we analyze the impact of learning from internationalization on small and medium enterprises' (SMEs) performance along different development paths. Drawing on the exploitation versus exploration logic, we use an alternative view of foreign operation modes (the learning perspective) to provide insights into the impact of such learning on technological and organizational innovation as well as overall performance. Our results, which are derived from a sample of 132 SMEs active in traditional manufacturing industries, point to a path to superior performance that entails resource-augmenting operation modes and organizational innovation.
Keywords: O31; F23; L25; M10; M16; 650; Exploitation; exploration; operation mode; innovation; organizational learning